PENGARUH MODEL PEMBELAJARAN PICTURE AND PICTURE TERHADAP KEMAMPUAN MENULIS TEKS INFORMATIF SISWA KELAS V SD NEGERI 165 PALEMBANG - Riska Ananda Natasya; Nuranisa; Hermansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The ability to write informative texts among Grade V students at SD Negeri 165 Palembang is still below the Minimum Mastery Criteria (KKM) standard. To address this issue, a study was conducted with the aim of improving students' writing skills by applying the Picture and Picture learning model. Until now, the lecture method used in the teaching and learning process tends to be monotonous and causes students to feel bored, resulting in learning outcomes that do not meet expectations. Therefore, a more engaging and effective learning strategy is needed. The implementation of the Picture and Picture model, which is relevant to the learning material, has proven to improve students' writing abilities. This study was carried out in three stages: pre-test, treatment, and post-test. Data analysis through percentage calculations showed an increase in students’ average scores after the treatment was applied. Thus, the Picture and Picture model has been proven to help improve the writing skills of Grade V students at SD Negeri 165 Palembang.